Corporate Governance Moderation in the Relationship between Compliance, Strategy, and Audit Quality on Tax Avoidance - Lanori, Tamrin; Adwimurti, Yudhistira; Lumbantobing, Sabar Pardamean (Jurnal Dinamika Akuntansi dan Bisnis, 2025)
This study investigates the influence of legal compliance, operational management strategies, and audit quality on tax avoidance, with corporate governance serving as a moderating variable. It explores how corporate governance mechanisms either amplify or mitigate the effects of these factors on tax avoidance in cyclical and non-cyclical companies listed on the Indonesia Stock Exchange. Employing a quantitative approach, the study analyzes cross-sectional data from 2023, covering 182 firms (98 cyclical and 84 non-cyclical). The results indicate that legal compliance and audit quality significantly reduce tax avoidance, whereas operational management strategies significantly increase it. Corporate governance moderates these relationships by strengthening the negative effects of legal compliance and audit quality and by attenuating the positive effect of operational strategies. Additional analysis shows that operational strategies exert a stronger influence on tax avoidance in cyclical companies than in their non-cyclical counterparts.